Defining movement strategies in soccer instep kicking using the relationship between pelvis and kick leg rotations - Augustus, S.; Hudson, P.; Smith, N. (Sports Biomechanics, 2022)
Growing evidence suggests skilled ball kickers use distinct pelvis and kick leg strategies to achieve successful performance. However, since the interaction between different strategies remains unexplored, the aims of this study were to a) examine relationships between pelvis and kick leg rotations in male players performing soccer instep kicks and b) classify different `types` of kickers based on the observed movement strategies. Twenty semi-professional players performed kicks for maximal speed and accuracy, and kick leg and pelvis kinematics were analysed using 3D motion capture (1000 Hz). A strong relationship was found between change in pelvis transverse angular velocity and thigh-knee angular velocity ratio upon ball contact (r = 0.76, p < 0.001), and participants were categorised by their location on kick leg (thigh-knee) and pelvis (maintainer-reverser) continuums. Knowledge of a player`s preferred strategy can inform departure from `one size fits all` technical and conditioning training practices towards more individualised approaches. For example, pelvis maintainer-thigh dominant kickers might benefit from focus towards the concentric capabilities of the hip flexors, whereas reverser-knee dominant kickers might benefit from developing the ability to decelerate the pelvis and thigh to induce motion-dependent angular acceleration of the lower leg towards the ball.